2007
DOI: 10.2166/wst.2007.393
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic oxidation of VX-simulation substance

Abstract: Experimental studies of photocatalytic oxidation (PCO) of VX-gas simulation substance cysteamine-S-phosphate sodium salt (NaHPO3S-CH2-CH2-NH2, CPSS) at various initial concentrations and pH were undertaken. PCO ultimately resulted in complete mineralisation of CPSS. The PCO byproducts of CPSS include acetate, oxalate and trace amounts of formate ions. The formation rates of acetate and phosphate were equal to the rate of degradation of CPSS, which indicates easy breakage of P-S, C-S and C-N bonds. Sulphate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The formation of terbufos-oxon (compound II) is attributed to oxidative desulfuration by • OH attack (Scheme 1, route A). Terbufos-oxon represents one of the most expected intermediates since previous studies showed that the oxidant attack of the • OH radicals on the P S bond occurs firstly in the case of phosphorothioates, resulting to the formation of the oxon derivatives [30,34,49,50].…”
Section: Initial Photooxidation Pathwaymentioning
confidence: 99%
“…The formation of terbufos-oxon (compound II) is attributed to oxidative desulfuration by • OH attack (Scheme 1, route A). Terbufos-oxon represents one of the most expected intermediates since previous studies showed that the oxidant attack of the • OH radicals on the P S bond occurs firstly in the case of phosphorothioates, resulting to the formation of the oxon derivatives [30,34,49,50].…”
Section: Initial Photooxidation Pathwaymentioning
confidence: 99%